Perspective: The Potential Effects of Naringenin in COVID-19 - Alberca, Ricardo Wesley; Teixeira, Franciane Mouradian Emidio; Beserra, Danielle Rosa; de Oliveira, Emily Araujo; Andrade, Milena Mary de Souza; Pietrobon, Anna Julia; Sato, Maria Notomi (Frontiers in Immunology, 2020)
Coronavirus disease 2019 (COVID-19), caused by Severe Acute Respiratory Coronavirus-2 (SARS-CoV-2), has been declared a pandemic by the World Health Organization in March 2020. Severe COVID-19 cases develop a severe acute respiratory syndrome, which can result in multiple organ failure, sepsis, and death. The higher risk group incudes elderly, and subjects with pre-existing chronic illnesses such as obesity, hypertension, and diabetes. To date, no specific treatment or vaccine is available for COVID-19. Among many compounds, naringenin (NAR) a flavonoid present in citrus fruits has been investigated for antiviral and anti-inflammatory properties like reducing viral replication and cytokine production.. In this perspective, we summarize NAR potential anti-inflammatory role in COVID-19 associated risk factors and SARS-CoV-2 infection.